HLA‐B27 prevalence in axial spondyloarthritis patients and in blood donors in a Lebanese population: Results from a nationwide study. (6th February 2019) - Ziade, Nelly; Abi Karam, Ghada; Merheb, Georges; Mallak, Iyad; Irani, Laure; Alam, Elie; Messaykeh, Jamil; Menassa, Jeanine; Mroue', Kamel; Uthman, Imad; Masri, Abdel Fattah; Ghorra, Pierre; et al.
Abstract: Aim: To calculate the prevalence of human leukocyte antigen (HLA)‐B27 in axial spondyloarthritis patients (axSpA) compared to blood donors (BD) in Lebanon, to identify the clinical and radiological findings associated with HLA‐B27 and to estimate the proportion of patients fulfilling the clinical arm of the Assessment of the Spondyloarthritis International Association (ASAS) criteria. Method: Consecutive Lebanese adult axSpA patients fulfilling the ASAS classification criteria were included from 12 rheumatology clinics across Lebanon. BD served as controls. A binary logistic regression was used to study the association between HLA‐B27 and the disease features. Results: A total of 247 individuals were included (141 axSpA patients and 106 BD). The prevalence of HLA‐B27 was 3.8% in BD and 41.1% in axSpA. Overall, 39.7% of the axSpA patients fulfilled the clinical arm of the ASAS classification criteria. Sensitivity of HLA‐B27 for axSpA was 41.1%, specificity was 96.2%, positive predictive value was 93.6%, and negative predictive value was 55.13%. Positive likelihood ratio (LR) was 10.9 and negative LR was 1.63. We found a positive association of HLA‐B27 with family history of SpA and psoriasis. Conclusion: Our study confirmed a low prevalence of HLA‐B27 in axSpA patients and BD in this Lebanese population, However, we found a high specificity and positive LR, as well as the same number of axSpA patients fulfilling the clinical arm of the ASAS criteria as in European studies. HLA‐B27 is therefore valuable for identification of axSpA in Lebanese patients despite the overall low prevalence in this population. Our results may guide future evaluations the role of HLA‐B27 in planning local referral strategies.